Concentration and velocity profiles in a polymeric lithium-ion battery electrolyte. Issue 11 (9th October 2020) - Steinrück, Hans-Georg; Takacs, Christopher J.; Kim, Hong-Keun; Mackanic, David G.; Holladay, Benjamin; Cao, Chuntian; Narayanan, Suresh; Dufresne, Eric M.; Chushkin, Yuriy; Ruta, Beatrice; Zontone, Federico; Will, Johannes; et al.
Abstract : Direct measurements of concentration and velocity profiles in a polymeric lithium-ion battery electrolyte provide insights into the transference number. Abstract : Predictive knowledge of ion transport in electrolytes which bridges microscopic and macroscopic length scales is imperative to design new ion conductors and to simulate device performance. Here, we employed a novel approach combining operando X-ray photon correlation spectroscopy, X-ray absorption microscopy, continuum modelling, and molecular dynamics simulations to probe the ion transport in a baseline polymeric lithium-ion battery electrolyte. In a Li/PEO–LiTFSI/Li symmetric cell under polarization, we determined and rationalized microscopic properties including local electrolyte velocities and ion correlations and connected this insight to measured and simulated macroscopic ion concentration gradients. By relating our results across length scales, we suggest a fairly concentration-independent transference number of about 0.2. Our study shows the broad applicability of operando X-ray photon correlation spectroscopy to the understanding of dynamic phenomena.